Effects Alkaliods extrects of Citrullus colocynthus fruits and seeds and Conocarpus erectus leaves on radial growth of Vicia faba seeds and roots compaing fungi - S. Saadon, Abdul ameer; Abdu Al-abaas, Duaa (Al-Qadisiyah Journal of Pure Science, 2018)
This study included the efficacy of the alkaloid , which extracted from leaves of Conocarpus erectus and fruits , seeds of Citrullus colocynthis and urea on the radial growth of Alternaria alternata and Aspergillus ochraceus isolated from seeds and roots of faba bean compared with fungicide Tapsin, also testing the effect of these treatment in germination of seeds in sterilized and un sterilized soil , and detection of tested fungi by molecular method using polymerase chain reaction( PCR). The results showed that the alkaloids have significant effect on growth of tested fungus on solid culture medium (PDA) , in measuring with controlled treatment and tested fungicide at level of possibility 5%, and also increasing the rate of germination of faba bean seeds in sterilized and un sterilized soil. The concentration 15mghad the greatest action comparing with other alkaloids and urea concentrations and fungicides. The testing of measuring Infra-Red Spectrum (FTIR) showed the presence of many specific band due the extraction alkaloids.